Mapping an epitope in EBNA‐1 that is recognized by monoclonal antibodies to EBNA‐1 that cross‐react with dsDNA. Issue 3 (2nd August 2016) - Yadav, Pragya; Carr, Matthew T.; Yu, Ruby; Mumbey‐Wafula, Alice; Spatz, Linda A.
Abstract: Introduction: The Epstein Barr Virus (EBV) has been associated with the autoimmune disease, Systemic Lupus Erythematosus (SLE). EBV nuclear antigen‐I (EBNA‐1) is the major nuclear protein of EBV. We previously generated an IgG monoclonal antibody (MAb) to EBNA‐1, 3D4, and demonstrated that it cross‐reacts with double stranded DNA (dsDNA) and binds the 148 amino acid viral binding site (VBS) in the carboxyl region of EBNA‐1. The aim of the present study was to characterize another antibody to EBNA‐1 that cross‐reacts with dsDNA, compare its immunoglobulin genes to 3D4, and finely map the epitope in EBNA‐1 that is recognized by these cross‐reactive antibodies. Methods: We generated an IgM MAb to EBNA‐1, 16D2, from EBNA‐1 injected mice and demonstrated by ELISA that it cross‐reacts with dsDNA and binds the 148 amino acid VBS. We sequenced the variable heavy and light chain genes of 3D4 and 16D2 and compared V gene usage. To more finely map the epitope in EBNA‐1 recognized by these MAbs, we examined their binding by ELISA to 15 overlapping peptides spanning the 148 amino acid domain. Results: Sequence analysis revealed that 3D4 and 16D2 utilize different VH and VL genes but identical JH and Jk regions with minimal junctional diversity. This accounts for similarities in their CDR3 regions and may explain their similar dual binding specificity. Epitope mapping revealed 3D4 and 16D2 bind the same peptide in the VBS. Based on the crystal structure of EBNA‐1, we observed that this peptide resides at the base of an exposed proline rich loop in EBNA‐1. Conclusion: We have demonstrated that two MAbs that bind EBNA‐1 and cross‐react with dsDNA, recognize the same peptide in the VBS. This peptide may serve as a mimetope for dsDNA and may be of diagnostic and therapeutic value in SLE. Abstract : We have mapped a peptide epitope in EBNA‐1 that is recognized by two monoclonal antibodies to EBNA‐1 that cross‐react with dsDNA. This epitope resides at the base of a proline rich loop in the viral binding site of EBNA‐1. It may serve as a mimetope for dsDNA and may be of diagnostic and therapeutic value in SLE.